Developing a management and finance training for future public health leaders - Hayes, Kristy T.; Heiman, Harry J.; Honoré, Peggy A. (Frontiers in Public Health, 2023)
Public health leaders are increasingly being asked to address adaptive challenges in the context of finite and often limited resources. Budgets and their associated resources create the financial framework within which public health agencies and organizations must operate. Yet, many public health professionals expected to undertake roles requiring this foundational knowledge and skills are not trained in the fundamentals of public finance and are ill-equipped for managing and monitoring funds. Graduate courses in schools of public health most often are focused on health care management and finance or private sector finance. To meet the needs of future public health leaders, it is critical that academic content builds capacity in management and finance focused on public health practice. This paper describes the development of a Doctor of Public Health program management and finance course designed to prepare future public health leaders. The course aims to build the knowledge and skills of doctoral-level students to recognize the inherent challenges of public health finance and the importance of cultivating and managing resources to improve public health practice and achieve strategic public health goals.